A novel flavivirus strain detected in phlebotomine sandflies in Bosnia and Herzegovina - Mirsada Hukić; Halida Avdihodžić; Ivan-Christian Kurolt; Alemka Markotić; Jasna Hanjalić; Lejla Kapur-Pojskić; Irma Mahmuljin; Monia Avdić; Irma Salimović-Bešić; Lejla Smajlović-Skenderagić (Medicinski glasnik, 2020)
Aim: Phlebotominae sandflies are primary vectors of phleboviruses, causing the sandfly fever disease. The aim of this study was to detect and report the presence of flaviviruses in Phlebotominae sandflies captured in Bosnia and Herzegovina. Methods: After a microscopic and morphometric analysis, the final identification of collected Phlebotomus specimens was confirmed by PCR, using a hemi-nested polymerase chain reaction on extracted and reversely transcribed RNA. Results: We obtained a 155 nt long fragment of the viral non-structural protein 5 (NS5) gene (GenBank accession no. MN090154). The acquired nucleotide sequence, provisionally named as Drežnica, showed a maximum of 70-80% identity in 70-88% (110-137 nucleotides) of the query coverage with several Anopheles, Sabethes, Calbertado and Culex flaviviruses. Maximum likelihood phylogenetic analysis showed that the new flavivirus Drežnica clusters together with the flavivirus isolated from Culiseta annulata mosquitos. Conclusion: We report the presence of flavivirus in Phlebotominae sandflies, captured in Drežnica, Herzegovina for the first time. The next phase of research will be directed towards virus cultivation, obtaining a longer or complete virus sequence and clarifying the medical and epidemiological importance of the Drežnica virus.
Keywords: arboviruses; Anopheles; mosquitoes; Phlebotomus; sandfly